Thermo-hydrous behavior of dried un-blanched potato samples. (January 2019) - Boutelba, I.; Zid, S.; Glouannec, P.; Youcef-ali, S.; Magueresse, A.; Kimouche, N.
Abstract: This study concerns a purely convective drying of parallelepiped un-blanched potato slices. A numerical model for heat and mass transfer has been developed in Lagrangian referential to overcome the structural changes. The thermo-physical properties of the slices vary with the temperature and moisture content. The finite volume method combined with a typically implicit time pattern was used to solve the model equations. The evaporated mass flux was calculated using the transfer surface area by which the water evaporates, and heat transfer coefficient was estimated using Nusselt number; The inverse method was used in this computation. The experiments were carried out under several thermo-aeraulics conditions in order to determine the most influent operating variable on the drying kinetic. A good agreement between experimental and simulated results was obtained with a moisture content determination coefficient ( R 2 ) higher than 0.9980; Whereas, the surface and center temperatures are higher than 0.9328 and 0.9305 respectively. The results have shown that the air temperature is the most important parameter that controls the drying kinetic. Highlights: Transport of heat and mass transfer inside the product. The effect of aerodynamic conditions on hydro-thermal transfer on the product. Water activity rate and the effective diffusion coefficient. Transfer surface area estimation and Nusselt number using inverse method. A confrontation between experiments and simulation of drying process.